Inventory Control at The Perintis Cimaung Pharmacy Using Open Source Enterprise Resource Planning System: Odoo 14.0 - Krisnawanti; Gia Ginasta, Nava; Faisal Nasrudin, Muhammad; Anis Nasution, Amida (RISTEC : Research in Information Systems and Technology, 2023)
Along with the times and technology, more and more companies are switching from manual mana gement of business processes to integra ted information systems. Perintis Pha rmacy is a pha rmacy located in the Bandung district. Perintis Pha rmacy has been serving its customers since 2010. However, Perintis Pha rmacy has experienced severa l problems, where all business processes a re still carried out manually. Errors frequently occur in both the service process and the inventory management system. Errors in stock ca lculations and ordering a re the ma in obstacles. This causes the Pha rmacy to experience losses both in terms of service quality and financia lly. So it is necessa ry to implement an integra ted system so that inventory management becomes more effective and efficient, namely the application of an Enterprise Resource Planning (ERP) system that is integrated with forecasting simulations to obtain a more accurate amount of drug procurement. Demand forecasting is done using Time Series data with the Single Exponentia l Smoothing method, given the fluctuating demand every month. Then the forecasting results are integrated with the ERP system using the Odoo 14.0 application in the invoice, purchase, and inventory modules. By using the Odoo 14.0 application, it is expected that Perintis Pha rmacy can increase efficiency and effectiveness in managing drug supplies so as to improve service quality and financial benefit s.